Optimization of the Role of Bhabinkamtibmas Through Counseling in the Prevention of Criminal Actions of Theft by Weighting in the Jurisdiction of the Sragen Police - Sitorus, Tiara (Advances in Police Science Research Journal, 2024)
Theft by weight is one type of conventional crime that still has a high number of cases in the jurisdiction of the Sragen Police. The Sragen Police Resort through Bhabinkamtibmas needs to play a role in preventing cases of criminal acts of theft with weighting by carrying out preemptive efforts through counseling. The implementation of socialization and counseling for bhabinkamtibmas in the jurisdiction of the Sragen Police (especially in Gedungupit, City of Sragen, and Kedawung) has been going well but not yet fully optimal. Based on data obtained from Sat. Sragen Police Criminal Investigation Unit that the number of theft crimes by weight at the Sragen Police Resort has fluctuated in the last 4 years. This situation motivated the author to conduct more in-depth research on the topic entitled "Optimizing the Role of Bhabinkamtibmas Through Counseling in the Prevention of the Crime of Theft with Weights in the Legal Territory of the Sragen Police." The research approach chosen is qualitative research and case studies, meaning that the author places himself as a research subject who goes directly to the field at the time of the research. In addition, this research is also supported by data collection techniques, namely observation, interviews, and documentation studies through documents which are then validated for truth through triangulation as well as determining the data to be used through data reduction, data presentation, and determining conclusions. The research findings are then reviewed and analyzed using management theory, work achievement factor theory, and SWOT theory. The results of the study found that the counseling activities carried out by Bhabinkamtibmas at the Sragen Police Station were not optimal so the crime of theft by weighting increased. Less than optimal activities carried out by Bhabinkamtibmas are caused by several factors, which consist of internal factors and external factors. So the researchers suggest that personnel comply more with the attention that has been given regarding picket assignments so that Bhabinkamtibmas can be more optimal in its performance.